No country for old men : from novel to film - King, Lynnea Chapman, 1967-; Wallach, Rick; Welsh, James M., 1938-2013 (Scarecrow Press, 2009)
"In 2005, Cormac McCarthy's novel, No Country for Old Men, was published to wide acclaim, and in 2007, Ethan and Joel Coen brought their adaptation of McCarthy's novel to the screen. The film earned praise from critics worldwide and was honored with four Academy Awards', including Best Picture, Best Director, and Best Adapted Screenplay. In No Country for Old Men: From Novel to Film, scholars offer varied approaches to both the novel and the award-winning film. Beginning with several essays dedicated entirely to the novel and its place within the McCarthy canon, the anthology offers subsequent essays focusing on the film, the adaptation process, and the Coen Brothers more broadly. The book also features an interview with the Coen brothers' long-time cinematographer Roger Deakins. This entertaining and enriching book for readers interested in the Coen Brothers' films and in McCarthy's fiction is an important contribution to both literature and film studies"--Provided by publisher